HYDROTHERMAL SYNTHESIS OF LOW SI/AL RATIO BEA ZEOLITE USING CONVENTIONAL AND TUBULAR AUTOCLAVE - Saputra, Yoni
The synthesis of low Si/Al ratio zeolite has many advantages including obtaining zeolite that has more acidic sites with a high Al content; the more hydrophilic nature of zeolite, making it suitable for use in reactions with aqueous media such as removal of hardness of water, absorption of ammonium and heavy metals in water; more ion exchange capacity; and smaller particle sizes thereby expanding the surface area and accelerating the reaction. BEA zeolite with a low Si/Al ratio is difficult to obtain conventionally because the synthesis of the zeolite involves the arrangement of a sufficient number of Al species in the zeolite framework. It is energetically easier to synthesize zeolite with a high silica content (excluding pure silica zeolite) than to synthesize zeolite with a high aluminum content, due to the larger (positive) entropy change of formation and Gibbs free energy change, which is more negative in zeolite with high Si/Al ratio. The difficulty of synthesizing zeolite with a low Si/Al ratio is in line with Löwenstein's law of "aluminum avoidance" where -Al-O-Al- bonding in the alumniosilicate structure is prohibited. These conditions make zeolite with more silica content than the amount of aluminum much easier to synthesize. In this study, various synthesis parameters were carried out in the form of Si/Al ratio, synthesis time, synthesis temperature, and variations in aluminum sources to obtain BEA zeolite with the lowest Si/Al ratio which can be synthesized under normal conditions hydrothermally using TEAOH as an organic structure directing agent (OSDA) without aging process. The ratio of TEAOH/SiO2 and NaOH/SiO2 are 0.12 referring to the ratio of Na to Si in the chemical formula of BEA zeolite, namely Na7[Al7Si57O128]. An attempt to synthesize zeolite with Si/Al ratio = 5 using Al(OH)3 and Ludox HS-40 as Al and Si sources in this study did not produce any zeolite framework products, even with a synthesis time of 96 hours. This is proven by the formation of an amorphous phase from the results of characterization using x-ray diffraction (XRD). BEA zeolite began to form at Si/Al ratio of 7.5 and synthesis time of 60 hours with crystallinity of 74.77%. Increasing the Si/Al ratio to 10 can shorten the time required for the synthesis of BEA zeolite to 48 hours while at the same time tending to increase the crystallinity of the resulting BEA zeolite. The shortest time needed to carry out the synthesis of BEA zeolite is 36 hours with minimum Si/Al ratio required of 12.5. Reducing the synthesis time to 24 hours did not produce BEA zeolite even though the Si/Al ratio had been increased to 30, indicating that the kinetic factor played an important role in the synthesis of zeolite. The BEA zeolite with the highest crystallinity that was successfully synthesized in this study was 92.79%, obtained at Si/Al ratio of 15 with synthesis time of 48 hours, which was then used as a reference for variations in synthesis temperature, aluminum sources and variations of tools used for zeolite synthesis. Increasing the synthesis temperature leads to the formation of MFI zeolite, indicating that BEA zeolite is kinetically favored but MFI zeolite is more thermodynamically stable. Variations in synthesis temperature and the use of Al2O3 as a source of Al lead to the formation of pentasil group zeolites, namely MFI, MTW, MOR, and quartz. The results show that the order of thermodynamic stability of product is quartz > MOR, MFI > MTW. Utilizing tubular autoclave as a synthesis tool led to the formation of one type of zeolite, namely MFI. Al2O3 as a source of Al was able to produce MFI zeolite within 2 hours, whereas by using Al(OH)3, the product was obtained with good crystallinity at a synthesis time of 8 hours. This shows that Al2O3 affects the kinetics by accelerating product formation. Zeolite synthesis using a tubular autoclave for 2 hours with an Al source in the form of Al2O3 produced spherical-shaped zeolite MFI nanoparticles. Meanwhile, an increase in synthesis time with the same synthesis parameters resulted in a high crystallinity MFI zeolite with a mixed morphology of beams and hexagonal shapes. Although the tubular autoclave is capable of accelerating the formation of zeolite, this method cannot facilitate the synthesis of BEA zeolite with a Si/Al ratio ? 5 up to 12 hours of synthesis time.